Triglyceride-glucose index correlates with the incidences and prognoses of cardiac arrest following acute myocardial infarction: data from two large-scale cohorts - Huiruo Liu; Liangshan Wang; Hong Wang; Xing Hao; Zhongtao Du; Chenglong Li; Xiaotong Hou (Cardiovascular Diabetology)
Abstract Background The triglyceride-glucose (TyG) index, renowned for its efficacy and convenience in assessing insulin resistance, has been validated as a reliable indicator for various cardiovascular conditions. The current study aims for clarifying the link of TyG with the incidences and prognoses of cardiac arrest (CA) following acute myocardial infarction (AMI). Methods Our analysis is a multicenter, retrospective study utilizing data from the Medical Information Mart for Intensive Care IV and the eICU Collaborative Research Database. Patients with AMI for whom TyG could be calculated within the first 24 h after admission were included. The main endpoints were in-hospital and ICU mortalities. Correlations between TyG and outcomes were evaluated using logistic regression models, restricted cubic splines (RCS), as well as correlation and linear analyses. Overlap weighting (OW), inverse probability of treatment weighting (IPTW), and propensity score matching (PSM) methodologies were utilized to balance the cohorts, thereby minimizing potential biases. Subgroup analyses were performed in accordance with identified modifiers. Results In total, 5208 individuals diagnosed with AMI, among whom 371 developed CA, were ultimately included. Higher TyG levels were observed among AMI populations with CA compared to those without [9.2 (8.7–9.7) vs. 9.0 (8.5–9.4)], and TyG demonstrated a moderate discriminatory capacity for identifying CA occurrences within entire AMI populations. Multivariate logistic regressions revealed TyG serves a significant risk indicator for both in-hospital (OR 1.711) and ICU mortalities (OR 1.520) in AMI-CA patients, and it is also associated with prolonged LOSs. RCS analyses confirmed linear relationships of ascending TyG with increased mortality risks for AMI-CA (P for nonlinearity: 0.592 and 0.816, respectively), which persisted following PSM, OW, and IPTW adjustments. Subgroup analyses further identified a strong link of the TyG with mortality rates among elders, females, individuals with BMI < 28 kg/m2, and those with hypertension. Conclusions Elevated TyG levels were found to apparently correlate with higher prevalence and adverse outcomes regarding CA in patients with AMI. Our findings point a fresh insight into the significance of the TyG in critically ill coronary conditions.